EFFECT OF FERTILIZER ELEMENTS ON LIPIDS ACCUMULATION AND FATTY ACIDS COMPOSITION OF PUMPKIN SEEDS - S. M. Nadezhkin; N. A. Golubkina; T. V. Kiseleva (Овощи России, 2015)
Effect of organic and mineral fertilizers on pumpkin seeds lipids accumulation and their fatty acids com position is investigated. The influence of nutrition's composition on the seeds size, lipids content and concentration of polyunsaturated fatty acids was shown.